Are clinical features in Löfgren’s syndrome-related erythema nodosum different from idiopathic erythema nodosum? - Dönmez, S.; Kisacik, B.; Nuri Pamuk, et al., Ö. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2012)
Background and Objectives:We retrospectively evaluated acute sarcoidosis (Löfgren’s syndrome) patients diagnosed at 2 centers and compared the clinical features of Löfgren’s syndrome (LS) related erythema nodosum (EN) to patients with idiopathic IEN who were diagnosed within the same time frame. Methods: Thirty patients (10 males, 20 females) who were diagnosed with LS and were being followed up for the last 8 years at 2 centers were included. Thirty patients (4 males, 26 females) who were admitted to the rheumatology outpatient clinics for IEN during that time period were taken as controls. The clinical and laboratory features at the initial admission, treatment modalities and response were recorded. Results: Twentyfour (80%) patients with LS related EN had arthritis and/or arthralgia. Fifteen of them had only findings of periarticular ankle inflammation and 4 had polyarthritis.When LS related EN patients were compared to IEN patients, the former group had more arthritis and/or arthralgia (p<0.001), leucocytosis (p=0.02), lymphopenia (p=0.005) and thrombocytosis (p=0.05), and higher ESR (p=0.02). Twentyfive (83.3%) patients with LS related EN were administered oral corticosteroids. In 21 patients, hilar lymphadenopathy disappeared on control chest x-ray and CT; in 3 patients, minimal residual lymph node enlargement was persistent. During a median follow-up of 54 months (range: 10-84 months), none of the LS related EN patients had clinical relapse. Conclusions: Apart from BHL, arthritis and/or arthralgia especially periarticular ankle inflammation is the feature which could be used to differentiate LS related EN from IEN. There is more need for steroids in LS patients and the symptoms quickly resolve with steroids.